Influence of the Lactotripeptides Isoleucine-Proline-Proline and Valine-Proline-Proline on Systolic Blood Pressure in Japanese Subjects: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. - Aurelie Chanson-Rolle; François Aubin; Veronique Braesco; Toshimitsu Hamasaki; Masafumi Kitakaze (PLoS ONE)
Background The lactotripeptides isoleucine-proline-proline (IPP) and valine-proline-proline (VPP) have been shown to decrease systolic blood pressure (SBP) in several populations, but the size of the effect varies among studies. We performed a meta-analysis including all published studies to evaluate the SBP-lowering effect of IPP/VPP in Japanese subjects more comprehensively. Methods and findings Eligible randomized controlled trials were searched for within four bibliographic databases, including two Japanese ones. Eighteen studies (including a total of 1194 subjects) were included in the meta-analysis. A random effect model using the restricted maximum likelihood (REML) estimator was used for the analysis. The analysis showed that consumption of IPP/VPP induced a significant reduction in SBP as compared with placebo in Japanese subjects, with an estimated effect of -5.63 mm Hg (95% CI, -6.87 to -4.39, P<0.0001) and no evidence of publication bias. A significant heterogeneity between series was evident, which could be explained by a significant influence of the baseline blood pressure status of the subjects, the effect of IPP/VPP on SBP being stronger in hypertensive subjects (-8.35 mm Hg, P<0.0001) than in non-hypertensive subjects (-3.42mm Hg, P<0.0001). Furthermore, the effect of IPP/VPP on SBP remained significant when limiting the analysis to series that tested the usual doses of IPP/VPP consumed daily (below 5 mg/d), with estimated effects of -6.01 mm Hg in the overall population and -3.32 mm Hg in non-hypertensive subjects. Conclusions Results from this meta-analysis show that IPP/VPP lactotripeptides can significantly reduce office SBP in Japanese subjects with or without overt hypertension, and for doses that can potentially be consumed as an everyday supplement. This suggests that these peptides could play a role in controlling blood pressure in Japanese subjects. The systematic review protocol was published on the PROSPERO register (CRD42014014322).